Zafar al-Mohsin Pirzada's Literary Translations: An Analysis - Sehar Ashraf; Dr. Almas Khanum (بازیافت)
The tradition of translation in Urdu literature is not very old but Urdu translation is fast setting its evolutionary stages۔ Most of the translations that have been done so far in Urdu have been from English to Urdu. Zafar al-Mohsin Pirzada's name is particularly noteworthy in urdu translation.  Zafar al-Mohsin Pirzada's first translated literary book is by Robert Bolt, who is one of the best play writers in English. Robert wrote a play a “Man for all seasons” in 1960. Zafar al-Mohsin Pirzada translated this book in 2013 which was published from the Institute of Compilation and Translation of Punjab University. The second literary translation is derived from Brazilian writer Paolo Quilo's novel “The Alchemist”. The novel was originally written in Portuguese while Pirzada translated the novel freely from English into Urdu. The purpose of the article under consideration is to examine the literary translations of Zafar al-Mohsin Pirzada intellectually and to highlight the literary importance of these translations and to analyse the subject of these translations.